2022
DOI: 10.3390/v14102117
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Spectrum of HIV-1 Resistance Mutations in the Siberian Federal District

Abstract: The Siberian Federal District is among the most affected regions with a high prevalence of HIV-infection and is characterized by high HIV-infection incidence rate and high mortality among the HIV-infected population. HIV drug resistance poses a major threat to public health and is associated with increased mortality, HIV incidence, and cost of epidemic control programs. A total of 1281 samples from HIV-infected patients were sequenced and analyzed with the DEONA and HIVdb Program to assess the prevalence of dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…One of the major challenges in the fight against HIV infection is the emergence of drug resistance, which poses a serious threat to public health. Several studies have shown an alarming increase in drug resistance to antiretroviral drugs, including acquired resistance, which complicates the effective treatment of the disease [1][2][3][4]. Indeed, the likelihood of developing resistance to at least one antiretroviral drug is high and can lead to treatment failure in about 65% of cases [5].…”
Section: Introductionmentioning
confidence: 99%
“…One of the major challenges in the fight against HIV infection is the emergence of drug resistance, which poses a serious threat to public health. Several studies have shown an alarming increase in drug resistance to antiretroviral drugs, including acquired resistance, which complicates the effective treatment of the disease [1][2][3][4]. Indeed, the likelihood of developing resistance to at least one antiretroviral drug is high and can lead to treatment failure in about 65% of cases [5].…”
Section: Introductionmentioning
confidence: 99%